Role of Reproductive Factors on the Risk of Endometrial Cancer in Nineveh Province, Iraq: A Case-Control Study (Journal of Fatima Jinnah Medical University, 2025)
ABSTRACTBackground: Endometrial cancer (EC) is the sixth most common cancer worldwide. This study aimed to evaluate the associations between reproductive risk factors and EC in Nineveh Province, north Iraq, due to limited research.Methods: The study was conducted from September 2024 to the end of the year, using a case-control design. It included 100 cases of histologically diagnosed EC from 2022 to 2024 and 200 age-matched controls admitted to hospitals in the same catchment area for non-neoplastic and non-gynecological conditions. Informed consent was obtained before the interviews. The association between risk factors and EC development was measured using odds ratios (OR) and 95% confidence intervals (CI), with P-values ≤ 0.05 considered statistically significant.Results: The study found that nulliparous women were present in 12/94 (12.77%) cases and 10/194 (5.15%) controls, with a risk nearly three times significantly higher than that of parous women (OR, 2.69; 95% CI, 1.12–6.48, P = 0.032). The mean number of children in cases (5.16 ± 2.45) was significantly lower (P = 0.001) than that in controls (6.51 ± 2.66), and the mean age at first birth was significantly higher in cases (23.13 ± 5.50, P = 0.001). However, there was no significant difference in the age at menarche and menopause between the cases and controls. Conclusion: Parity and first-age delivery differed significantly among study participants. However, the age of menarche and menopause is not associated with increased EC risk
Keywords: Endometrial cancer; Reproductive factors; Parity, Age at first birth; Age at menarche; Age at menopause